Development of Language Learning Based on Multimedia Devices for Autistic Student - Nara, Hartini; Nomida Musnir, Diana; Situmorang, Robinson (KnE Social Sciences, 2020)
The purpose of this study to develop a learning device of Indonesian language based on multimedia for autistic students. This research was conducted at SD Islam Alam dan Sains Al- Jannah. The students involved in the research were 20 students. The developed learning device uses the instructional model approach by Dick Carey and Carey (2009). Subjects of the research were 20 students. The developed learning device consists on applications, videos and manual book for both student and teachers. The developed products have been reviewed by a subject matter expert, an instructional design expert, a language expert, a media expert and an information technology expert. A series of formative evaluations through try-out examination has been conducted. The improvement of the learning device has been developed based on the previous formative evaluations. The results of this study shows developed learning device could improve the student learning outcomes effectively. Based on this result, the learning device could be recommended to be used as an alternative learning resource. Keywords: development of learning devices, autistic student, Indonesian language, multimedia